Fundamentalism: Study of Islamic History - Djamiatul Islamiyah (Islah: Journal of Islamic Literature and History, 2020)
This paper is a literary study by analyzing various thoughts from various readings. The concern of this study is about fundamentalism in the study of Islamic history. The discussion material includes; contextualization, history and various thoughts in response to fundamentalism. Regarding contextualization, a discussion arises whether fundamentalism exists as a product, as an agent, or both? If it is related to social changes in Islamic society in particular. Is Islamic fundamentalism more of a religion matters? Some refer to the events of the Iranian revolution in 1979, to the 18th century Wahhabi movement, some others point to the Al-Mihnah policy by the Mu'tazilah during the reign of the caliph Al-Ma'mun in the 9th century. There are even those who say that the genealogy of fundamentalism has existed since the beginning of Islamic history, namely the emergence of the Khawarij which is seen as having the same qualifications as contemporary fundamentalism. Responses to fundamentalists have been written in various ways, such as the assumption about the hegemonic nature of Western civilization which is said to be an obstacle to the accommodation of the basics of mutual equality, as well as an attitude of mutual respect and recognition. Other responses were in the form of proposals for the deconstruction of fundamentalism, the idea of developing Islamic values of compassion and moderation as a way or policy of dealing with fundamentalism.